A Narrative Oriented Inquiry into emotionally based school avoidance: hearing the voices of young people and their parents - Want, Hannah (2020)
The majority of research into Emotionally Based School Avoidance (EBSA) has sought the views of adults and professionals, meaning the current understanding of the phenomenon is largely shaped by adult interpretations (Baker & Bishop, 2015). An emerging research base has begun to explore the pupil and parent voice regarding their experiences of EBSA and their perceptions of the future, however, this base is limited and predominantly utilises semi-structured data collection methods, therefore, potential depth and detail in the accounts of this vulnerable group is minimised.